IMPACT OF CLINICAL FEATURES ON QUALITY OF LIFE IN WOMEN WITH POLYCYSTIC OVARIAN SYNDROME - SRI CHANDANA MAVULATI; SUJATHA DODOALA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The primary objective of the study focuses on measuring the quality of life (QoL) in the study population using the polycystic ovarian syndrome questionnaire (PCOSQ). The secondary objective is to assess and correlate the impact of clinical features presented in affected women on QoL. Methods: A prospective, cross-sectional study was conducted involving 354 patients diagnosed with the syndrome. Clinical symptoms, demographic features, and QoL indicators were noted and evaluated using patient case history and PCOSQ. Statistical analyses such as analysis of variance, the Kruskal–Wallis test, and multiple regression statistics were conducted to evaluate the effect of clinical factors on QoL domains. Results: Five domains of health-related QoL (HRQoL) were assessed, signifying reduced QoL among the affected population. Hirsutism had the greatest impact on the study population (5.88±1.38). Emotional well-being was notably affected, with a moderate mean score of 4.34±1.30, influenced by hormonal imbalances and reproductive concerns that contributed to psychological distress. Weight issues (5.18±1.95) were positively correlated with acne severity (β=0.010, p<0.05), and menstrual distress (4.44±1.23) showed a negative association with body mass index (β=−0.018, p<0.05). Both weight concerns and menstrual irregularities contributed to reduced self-esteem and overall health of women. Evaluation of HRQoL across four phenotypes reported that phenotype A exhibited the poorest QoL across all the domains (p<0.05). Conclusion: PCOS is a multifactorial disease that impairs the QoL in affected women. The study results emphasize the need for targeted management, therapeutic and non-pharmacological, for improving the patient’s overall well-being.